Pengembangan Media Pembelajaran Games Book Accounting Untuk Meningkatkan Motivasi Mata Pelajaran Akuntansi Dasar Materi Siklus Akuntansi - Nailariza Umami; Muhammad Isna Nur Adha (Jurnal Pendidikan Ekonomi, 2021)
Education is the most important part in human life, because education is the determining factor for the progress of a nation.  Learning in schools should be done with innovative, varied, and can encourage students to be active and interactive.  But the fact is not as expected, because today there are still many who use conventional methods.  The aim of this research is to develop teaching materials in the form of Games Book Accounting for Basic Accounting subjects in the Accounting Cycle material for grade X Accounting students of SMKN 2 Trenggalek, and to determine the feasibility of the product based on the validation assessment of material experts, media experts, accounting learning practitioners.  This research is a research and development (R&D) that was adapted from the ADDIE model.  Which has 5 Stages, namely: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation, but only carried out until the third stage, namely Development.  This media has not been tried out to students because of time constraints as well as situations and conditions that are not possible, considering this research was made during the covid-pandemic conditions.  The results showed that the level of eligibility of Games Book Accounting teaching materials based on the assessment of validation was in the category of suitable for use with a very good predicate in accordance with the eligibility criteria and product revisions. DOI: https://dx.doi.org/10.17977/UM014v14i12020p15